2013
DOI: 10.1007/s00198-013-2595-z
|View full text |Cite
|
Sign up to set email alerts
|

Percentage of the population at high risk of osteoporotic fracture in South Korea: analysis of the 2010 Fifth Korean National Health and Nutrition Examination survey data

Abstract: As a very large percentage of the South Korean postmenopausal population has osteoporosis or high-risk osteopenia, greater effort at identifying and treating this population should be expended to prevent osteoporotic fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…We also observed that when the same age groups were compared, the Ca/P ratio increased in favour of Ca at advanced ages. While these results are similar to those of Kim et al [20] and Maharlouei et al [27], they contradict the results of Basle et al [1]. The reason for this inconsistency may be because Basle et al [1] studied a broad age interval including ages from 31 to 87.…”
Section: Discussionsupporting
confidence: 70%
“…We also observed that when the same age groups were compared, the Ca/P ratio increased in favour of Ca at advanced ages. While these results are similar to those of Kim et al [20] and Maharlouei et al [27], they contradict the results of Basle et al [1]. The reason for this inconsistency may be because Basle et al [1] studied a broad age interval including ages from 31 to 87.…”
Section: Discussionsupporting
confidence: 70%
“…According to data from the fifth Korean National Health and Nutrition Examination survey (KNHANES) in 2010, the percentages of the population with osteoporosis among elderly men and women aged over 65 years were 15.2% and 57.7%, respectively [17]. In Korea, the prevalence of osteoporotic fractures is increasing with the rapid growth in the elderly population [18, 19].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of osteoporosis and osteoporotic fractures, which are common metabolic conditions associated with aging, is dramatically increasing due to rapidly aging populations in most developing and developed countries. Since osteoporotic fractures not only reduce quality-of-life but also increase medical and health care expenses, this condition imposes a significant healthcare and financial burden [1,2].…”
Section: Introductionmentioning
confidence: 99%